Sharia Bank Policy In Restructuring And Rescheduling Processes For Customers Affected By The Spread Of Covid-19 - Fadia Fitriyanti; Ananda Prasetya Utami; Nisa Nurhofipah Ramadani; Erlangga Aryo Nugroho; Muhammad Ervizal Rizqi Pane (Universitas Muhammadiyah Surabaya, 2021)
The Covid-19 virus is an epidemic that has hit all countries in the world, including Indonesia. Almost all aspects of life are disadvantaged, such as the political, social, cultural, religious and economic fields. This pandemic situation has a direct impact on the weakening of the banking system, especially Islamic banking in Indonesia. The government has made regulations governing state finances, namely Government Regulation in Lieu of Law Number 1 Year 2020 and Financial Services Authority Regulation Number 11 / POJK.03 / 2020. The two regulations apply as credit restructuring or financing and rescheduling for those affected by the Covid-19 pandemic. This study aims to analyze the differences in the rescheduling and rescheduling process in Islamic banks before and during the Covid-19 period, and the strategy of Islamic banks in dealing with Covid-19. The methodology used in this research is normative legal research refresh law and book literature. The result of the research is the government through the OJK must supervise the activities carried out by various banks so that finances in Indonesia become stable even in a pandemic situation.